Factors Influencing the Pursuit of Legal Rights by Burn Victims of Domestic Violence - Zulfiqar Ali Buzdar, Javaid Munir, Remsha Fatima (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The decision to report domestic violence incidents, including burns, can be complex and influenced by various factors such as lack of confidence in police, delay in delivery of the just and social factors like that of fear, shame, and a belief that the family might be disturbed. Understandingthis trend is crucial in developing effective strategies to support and protect survivors. In matters of domestic violence of burns the victims fear to register the case in police station or any health facility. Aim: To understand the factors responsible for the failure of registering their burn incident as medicolegal issue. Methodology: Study was carried out among the victims of burns of domestic violence in the catchment area of May Hospital Lahore.The population of study comprises of urban and rural populations. The study sample comprised of 450 unfortunate victims of domestic burns for one whole year of 2018 from January to December brought in the Medicolegal Clinic of the King Edward Medical University Lahore. The data was collected on a predesigned questionnaire after due approval from Ethical Review Committee and Institutional Review Board. Results: The study results revealed that literacy level play a pivotal role in registering the incident of domestic violence a matter of legal concern being significant with a p value as 0.029. The social factors like that of confidence in the local police, the delay of the justice system and physical or emotional disturbance of the family if the fight for a legal battle in criminal domestic burn incident was found grossly significant with p value as 0.000 being very valid in growing economies. Conclusion: The study was found conclusive that literacy level and social factors like that of confidence in local law enforcement agencies, delay in delivery of the justice and family issues are the most vital social factors hindering to fight a legal battle in domestic burn incidents. Keywords: Burns, Domestic Violence, Legal Rights, Law Enforcement, Medicolegal Burns, Justice System